The role of aggregate preferences for labor supply: evidence from low-paid employment - Haywood, Luke; Neumann, Michael (Berlin, 2017)
"Labor supply in the market for low-paid jobs in Germany is strongly influenced by tax exemptions - even for individuals to whom these exemptions do not apply. We present compelling evidence that an individual's choice set depends on other workers' preferences because firms cater their job offers to aggregate preferences in the market. We estimate an equilibrium job search model which rationalizes the strong earnings bunching at the tax exemption threshold using German administrative data. We then simulate modifications to the tax schedule that remove the discontinuity and thus the bunching at the threshold. Results highlight the indirect costs of (discontinuous) tax policies which are shown to be reinforced by firm responses: Workers who would work anyway are hurt by subsidies benefiting groups who enter the market as a result of tax incentives."